SWOT ANALYSIS DEVELOPMENT OF WAY BELERANG TOURISM KALIANDA LAMPUNG SELATAN - Novalia; Yusuf, Muhammad; Anum, Adelina; Saleh, Khairul (Journal of Social and Economics Research, 2024)
The aim of this research is to determine the Way Sulfur tourism development strategy in increasing tourists in the South Lampung Regency Regional Government Environment using SWOT analysis. SWOT is an abbreviation for Strengths, Weaknesses, Opportunities and Threats. SWOT analysis is an analysis used in management and strategic planning to evaluate the situation or position of a business, project, product or other entity. The type of research used is descriptive qualitative. Qualitative research is often called the ethnographic method, phenomenological method, or impressionistic method, and other similar terms. Data collection methods in research can be secondary data and primary data. The data collection techniques used in this research are observation, documentation, questionnaires and interviews. After analyzing the data, it was found that the abscissa value (X) was 4.188 and the ordinate value (Y) was -2.021, so the value (X,Y) = ((4.188), (-2.021)). The abscissa value shows a positive value, while the ordinate value shows a negative value, so it is located in Quadrant II. The appropriate Way Sulfur Tourism development strategy is a diversification strategy or S-T strategy. In this strategy, what must be done is to use force to overcome threats.